Analysis of the Flavor Quality of Coffee Using Multiple Omic Technologies Combined with Electronic Sensory Detection Technology - LI Yulian, ZHENG Jianyi, HUANG Xuhui, DONG Xiuping, ZHAO Baomin, QIN Lei (Shipin Kexue, 2023)
By the combined use of metabolomics, flavoromics, and rapid electronic sensory detection technology, this study identified and analyzed the differences in flavor quality of six coffees. The results suggested that 2,6-dimethylpyrazine, 2-ethylhexan-1-ol, acetoin, isovaleric acid, and methyl valerate could be employed as aroma markers to distinguish coffees with different degrees of roasting. Additionally, 48 compounds, including guanine, tryptophan-alanine, crotonic acid, and 1-methyladenosine, were found to be the metabolic difference indicators to distinguish coffee powder from different geographical origins and their mixed samples. The major taste compounds of lightly roasted coffee were 1,4-D-xylose, alanine, isoleucine, and phenylalanine. Maltotriose was found to be a major compound in moderately roasted coffee, which also contained a lesser amount of inosine. The combination of electronic nose and electronic tongue detection with principal component analysis (PCA) could be used for rapid classification and variety identification of coffee. These results provide a theoretical basis and technical support for the production of coffee as well as a reference for establishing standards to evaluate the flavor and quality of coffee.